2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin-induced hypertension: The beneficial effects of melatonin. (April 2015) - İlhan, Selçuk; Ateşşahin, Dilek; Ateşşahin, Ahmet; Mutlu, Emre; Onat, Elif; Şahna, Engin
Objective: The purpose of the present study was to evaluate the effects of melatonin on biochemical and cardiovascular changes resulting from exposure to 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD), a polychlorinated dibenzo- para -dioxin. Methods: A total of 24 Sprague-Dawley rats were divided equally into the following four groups: (1) control group was administered with 0.5 mL corn oil by gavage and 0.5 cc vehicle of melatonin (proportionally nine parts physiological serum + one part ethyl alcohol) intraperitoneally for 4 weeks, (2) the melatonin group was given 5 mg/kg/day melatonin intraperitoneally for 4 weeks, (3) the TCDD group was given 500 ng/kg/day TCDD by gavage for 4 weeks and (4) the TCDD + melatonin group was given TCDD (500 ng/kg/day) by gavage and melatonin (5 mg/kg/day) intraperitoneally simultaneously for 4 weeks. Systolic blood pressure was evaluated by the tail-cuff method. Vascular responses to phenylephrine and acetylcholine were evaluated in the isolated thoracic aortas. Results: TCDD not only augmented the systolic blood pressure but also increased the contractile responses to phenylephrine in aorta. Melatonin reversed the blood pressure augmented by TCDD and decreased the contractile responses to phenylephrine in aorta. TCDD induced an increase in the malondialdehyde levels in kidney tissue and melatonin did not change it. Therefore, TCDD caused a decrease in glutathione levels in kidney tissues and melatonin reversed it. Conclusion: Present data demonstrated that TCDD may lead to an increase in blood pressure via increased renal oxidative stress and vascular reactivity. However, melatonin might ameliorate the blood pressure disturbed by TCDD in part by decreasing the oxidant activity induced by TCDD.